The expansion of economic protection for older adults in Latin America - Arza, Camila (2017)
Over the past two decades, many Latin American countries have expanded the economic protection of older adults by developing non-contributory pensions or making eligibility rules more flexible. These policies have addressed long-standing coverage gaps in Latin American pension systems and contributed to incorporating a large number of older adults in the social protection system. The paper examines the main design features of non-contributory pensions and how they interact with pre-existing contributory systems. It identifies the different types of coverage expansion strategies across Latin America and discusses three different country experiences (Argentina, Bolivia, and Colombia) in greater detail.